Lemongrass as anticandida: Serai sebagai anticandida - Sri Fatmawati Tulen; Nur Laila Umafagur; Nur Athaya Syam; Sitti Fadhillah Oemar Mattaliti (Makassar Dental Journal, 2021)
Lemongrass is one of the essential oil-producing plants. The main components of lemongrass are citronella and geraniol, which have an antifungal function. The Candida albicans is an opportunist fungus of the genus candida and are among the normal flora plants found in the human mouth. The candidiasis that attacks many communities are the oral candidiasis which occurs due to the disabling infections resulting from the abnormal growth of the growth of the C.albicans. Various studies have been conducted to extract lemongrass. This article explains several studies that have extracted lemongrass which is used to detain the C.albicans.